Risk Factors and Spatio-Temporal Patterns of Human Rabies Exposure in Northwestern Tigray, Ethiopia - Gebreyohans Gebru; Gebremedhin Romha; Abrha Asefa; Haftom Hadush; Muluberhan Biedemariam (Ubiquity Press, 2019)
Background: Rabies is a neglected tropical disease, which is economically important with great public health concerns in developing countries including Ethiopia. Epidemiological information can play an important role in the control and prevention of rabies, though little is known about the status of the disease in many settings of Ethiopia. The present study aimed to investigate the risk factors and spatio-temporal patterns of human rabies exposure in Northwestern Tigray, Ethiopia. Methods: A prospective study was conducted from 01 January 2016 to 31 December 2016 (lapsed for one year) at Suhul general hospital, Northern Ethiopia. Data of human rabies exposure cases were collected using a pretested questionnaire that was prepared for individuals dog bite victims. Moreover, GPS coordinate of each exposure site was collected for spatio-temporal analysis using hand-held Garmin 64 GPS apparatus. Later, cluster of human rabies exposures were identified using Getis-Ord Gi* statistics. Results: In total, 368 human rabies exposure cases were collected during the study year. Age group of 5 to 14 years old were highly exposed (43.2%; 95% CI, 38.2-48.3). Greater number of human rabies exposures was registered in males (63%; 95% CI, 58.0-67.8) than females (37%; 95% CI, 32.1-42.0). Residents of rural (85.6%; 95% CI, 81.6-88.8) areas were at greater risk to rabies than urban residents (14.4%; 95% CI, 11.2-18.4). Higher proportion of human rabies exposures were caused by unprovoked (96.5%; 95% CI, 94.0-98.0) and unvaccinated (85.9%; 95% CI, 81.9-89.1) dogs. All rabies exposures were exclusively caused by dog bites and the majority of them (80.4%; 95% CI, 76.0-84.2) were caused by stray dogs. Results of spatio-temporal analysis showed that Asgede Tsimbla, Endaselassie and Laelay Adiyabo districts experienced the highest burden of rabies exposure; identified as hot spots. Strong peaks of human rabies exposure occurred between March and July months. Conclusion: The present study provided basic epidemiological information on the potential risk factors associated with human rabies exposure. Moreover, our findings provided basis for understanding the spatio-temporal patterns of human rabies in Northwestern Tigray districts for the first time.